2008
DOI: 10.1186/1471-2407-8-179
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 is highly expressed in renal cell cancer and is associated with tumour progression

Abstract: Background: A Disintegrin And Metalloprotease (ADAM) 9 has been implicated in tumour progression of various solid tumours, however, little is known about its role in renal cell carcinoma. We evaluated the expression of ADAM9 on protein and transcript level in a clinico-pathologically characterized renal cell cancer cohort.Methods: 108 renal cancer cases were immunostained for ADAM9 on a tissue-micro-array. For 30 additional cases, ADAM9 mRNA of microdissected tumour and normal tissue was analyzed via quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 51 publications
6
51
0
1
Order By: Relevance
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…O'Shea et al [7] and Lendeckel et al [17] reported that ADAM9 mRNA and protein expression was increased in human breast cancer tissue. ADAM9 mRNA was also found to be significantly upregulated in renal cancer tissue compared with adjacent normal tissue [21]. Immunohistochemical analysis revealed that ADAM9 protein expression was significantly associated with higher tumor grade, positive nodal status, distant metastasis, and reduced patient survival [21].…”
Section: Discussionmentioning
confidence: 97%
“…ADAM9, a member of the ADAM family, has been demonstrated to be upregulated in a range of types of human cancer, including renal cell cancer (35), prostate cancer (36), breast cancer (37), hepatocellular carcinoma (38), and pancreatic cancer (39). Previous studies have also identified miRNAs that may interact with ADAM9.…”
Section: Discussionmentioning
confidence: 99%